An investigation of two methods for the technological mediation of collaborative peer feedback in higher education - Pavlou, Andria; Kyza, Eleni A. (My University, 2013)
Even though several studies have examined peer feedback through synchronous and asynchronous communication within the context of distance learning, few have addressed its contribution in higher education face-to-face settings. This proposal addresses this gap by examining peer feedback mediated through synchronous and asynchronous communication in the context of a face-to-face university course. Thirty-five undergraduate students participated in this study to provide feedback to each other's work through synchronous (chat) or asynchronous collaboration (in-context commenting). A variety of data were collected and included pre- and post-course surveys, videos and student interviews. The analysis of the results showed that students take advantage of the feedback they receive from their peers. As findings showed, peer feedback through asynchronous communication helped students learn, while peer feedback, mediated through synchronous tools, was important for interpersonal communication. Even when the feedback was not used to improve course work, students took it into serious consideration.
Keywords: Asynchronous communication; Peer feedback; Synchronous communication